ChemInform Abstract: On the Preparation and Structure of Caesium Aluminium Tetrahydride. Issue 5 (February 2015) - Krech, Daniel; Zibrowius, Bodo; Weidenthaler, Claudia; Felderhoff, Michael
Abstract CsAlH4 is synthesized by ball‐milling of stoichiometric mixtures of NaAlH4 and CsCl followed by dissolution of the obtained material in diglyme and subsequent precipitation with toluene or pentane.